Female political influencers in Argentina and Spain: Otherness in digital political scenarios - Slimovich, Ana (2025)
This paper analyzes the communication of female political influencers on TikTok, based on the assumption that, due to their gender, they represent otherness on social media. The characteristics of their communication styles, the performance on TikTok of four female political influencers from Spain and four from Argentina were explored. This is a cross-sectional, descriptive, exploratory research. The content analysis method was applied to the selected publications. The total sample is made up of 400 units of analysis, drawn from the universe of publications made on TikTok by eight female political influencers from Argentina and Spain. Fifty videos were analyzed for each influencer selected, in the context of national-level electoral campaigns in both countries. In the case of the Spanish women, the data collection period consisted of fifty videos published by each of them before 23 July 2023 inclusive, the date of the general elections in Spain. With reference to the Argentinian women, 50 videos published by them before and including 13 August 2023, the date of the PASO (Simultaneous Open Primary Elections) in Argentina, were collected. The results allowed us to identify their preferences in the types of videos they produce, classify the types of emotions they communicate, the main contents they choose to disseminate, as well as the degree of personalization that characterizes their clips.